On Doing Local History - Kammen, Carol (Rowman & Littlefield Publishers, 2014)
For over thirty years, Carol Kammen’s On Doing Local History has been a valuable guide to professional and “amateur” historians alike. First published in 1986, revised in 2003, this book offers not only discussion of practical matters, but also a deeper reflection on local, public history, what it means, and why it is done. It is used in classrooms and found on the shelves of local historians across the U.S. The third edition features: Updates to chapters that focus on the current concerns and situation of local historians A new chapter on how the field of history cooperates with other arts A new chapter on writing a congregational history Updated references With the same passion (and now even more experience) that drove her to write the first edition, Kammen has brought her seminal work into today’s context for the next generation of local historians. The new edition ensures that this classic will continue to move anyone interested in public history towards a better understanding of why they do what they do and how it benefits their communities.